From Collective Shiva to a Fast for the Ages: Religious Initiatives to Commemorate and Mourn the Victims of the Holocaust, 1944–1951 - Yedidyah, Asaf (Religions, 2022)
Religious Jewish tradition has specific rituals for mourning the loss of a relative. They include receiving visitors during shiva, the recitation of the Kaddish in the first year, and the annual marking of the Yahrzeit. There are also customs for commemorating collective disasters. Foremost among them are the diminution of joy on specific dates, and setting permanent fast days. Towards the end of World War II, when the extent of the destruction became apparent, initiatives began around the world to process the collective mourning and to perpetuate the disaster in religious settings. Many survivors later joined these initiatives, seeking to establish new customs, out of a deep sense that this was an unprecedented calamity. The growing need to combine private and collective mourning stemmed from an awareness of the psychological and cultural power of private mourning customs. Proposals therefore included the observance of a community yahrzeit, a collective Jewish shiva, along with a fast for the ages. This article explores the initiatives undertaken between 1944 and 1951—the time when intensive processing was needed for the survivors and the relatives of those who had perished—discussing their motivations, unique characteristics, successes and failures, and the reasons for them.